2018
DOI: 10.3389/fdigh.2018.00020
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Fibers—The Implications of the Digital for Archival Access

Abstract: This article explores how current methods and approaches in archives are under serious challenge because of the changes brought about by the move to the digital. The availability of digital records has meant that new needs and new possibilities have opened up for users, including new ways of reading. The nature of archives themselves are changing-they are moving from being collections of individual texts to be pored over to data to be made sense of. New tools and techniques have emerged and are available now w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Studies have drawn attention to the gulf that can exist between the perceived and actual needs of those who use digitised cultural heritage materials (Lynch 2003;Moss et al 2018). As it stands, all our interviewees reported that they make use of qualitative and quantitative information about user behaviour to shape delivery methods.…”
Section: The Algorithmic User: Tracking and Its Consequencesmentioning
confidence: 90%
See 2 more Smart Citations
“…Studies have drawn attention to the gulf that can exist between the perceived and actual needs of those who use digitised cultural heritage materials (Lynch 2003;Moss et al 2018). As it stands, all our interviewees reported that they make use of qualitative and quantitative information about user behaviour to shape delivery methods.…”
Section: The Algorithmic User: Tracking and Its Consequencesmentioning
confidence: 90%
“…These trends suggest that some providers will move beyond their current offerings and facilitate greater interaction and new forms of exploration, like cross-collection search and semantic web capability (see also Horrocks 2014;Moss et al 2018). By the same token, if paying subscribers expect an archive that is easy to use, with a simple interface, then it is not surprising that user interaction will remain limited to this form of interaction.…”
Section: Information Search and Retrievalmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the context-driven approach to archival research, embodied in the finding tool of archival inventories, reflects but one possible way to search aggregates of documents for specific information. Alternatives require, instead, a shift toward a content-driven approach (Moss et al, 2018). As archives become digitized, the issues of transparent and effective access become increasingly important.…”
Section: Approachmentioning
confidence: 99%
“…A great range of methods have been developed over the years to support the processing of email data, whether by data cleaning (Tang et al 2005), collation/classification (Mujtaba et al 2017), analysis (Borden and Baron 2016) or visualisation such as graphical or other visual representations of data or information (Repke and Krestel 2018). Visualisations, in particular, have regularly been employed as a method for exploring email collections and supporting the identification of high level patterns within a data-set (Louis and Engelbrecht 2011;Kaczmarek and West 2018;Moss et al 2018;Stadlinger and Dewald 2017). This practice is slowly migrating into the archival setting (Josh Schneider et al 2017) with the intention of supporting a holistic, creative, perhaps even 'playful' (Hendery and Burrell 2019) research.…”
Section: Introductionmentioning
confidence: 99%